Inactivation of faecal pathogens during faecal sludge composting: a systematic review. Issue 1 (31st December 2023) - Manga, Musa; Muoghalu, Chimdi C.; Acheng, Pamela O.
ABSTRACT: Feacal sludge (FS) management is a growing concern in the Global South. Research has shown that FS has a potential for reuse in agriculture due to its high nutrient content. However, it contains many pathogens which present a public health and environmental risks when it is applied to land without proper treatment. Composting is one of the viable options for sanitizing FS biosolids before reuse in agriculture as a soil conditioner. However, pathogen die-off during FS composting and factors responsible for pathogen survival in compost are not well understood. Therefore, we conducted a systematic review to better understand pathogen inactivation during FS composting. The results revealed that although most pathogens are inactivated by the temperature generated during composting, spore-forming bacteria, helminths, and viruses are likely to survive the process. The findings indicated that although temperature-time is the major factor responsible for pathogen inactivation during composting, other factors (change in pH, moisture content, turning frequency, nutrient depletion, toxic by-products) and mechanisms (indigenous microbial activities, microbial antagonistic effect, antibiotic action) also have an influence. In addition, most studies on pathogen inactivation during FS composting are usually based on the use of indicator microorganisms and there are limited studies on specific pathogens. Hence, further research on virus, protozoa and antimicrobial resistance inactivation during FS composting as well as the role of factors and mechanisms involved in the composting process is needed. This research will generate vital formation to inform the design, operation, and optimization of FS composting facilities to produce pathogen-free compost. GRAPHICAL ABSTRACT: UF0001